(untitled) (Journal of the College of Basic Education, 2025)
The current study aims to identify the effectiveness of the Reasoning Trial Strategy in developing literary appreciation skills among fifth-grade science female students. To achieve this, the researcher adopted a quasi-experimental design with two groups (experimental and control) using a post-test only. The sample consisted of 63 students—32 in the experimental group and 31 in the control group. Equivalence between the groups was ensured in variables such as chronological age (in months), mid-year Arabic language grades, Raven’s Progressive Matrices (IQ), linguistic ability, and a pretest for literary appreciation. The experimental group was taught using the Reasoning Trial Strategy, while the control group followed the traditional method. A total of 18 lesson plans were prepared for each group, and 90 behavioral objectives were formulated based on Bloom’s six levels of cognitive domain, and reviewed by experts for validity. Two tools were developed to measure literary appreciation (a post-test and a delayed test), each consisting of 22 multiple-choice items. Both instruments were validated for content and face validity, and their psychometric properties—difficulty index, discrimination index, and distractor effectiveness—were calculated. The reliability of the post-test was (0.88) and the delayed test (0.86), using Kuder-Richardson Formula 20. Results were statistically analyzed, leading to conclusions, recommendations, and suggestions for future research.